A study of the collaborative process of volunteers in a literacy intervention programme in support of vulnerable children in South Africa - Zoetmulder, Amy (Department of Health and Rehabilitation Sciences, 2020)
The development of early literacy skills is critical for all children in South Africa. Children receive language and literacy development support in the home, school, and community environments. Vulnerable children, such as orphans, may receive this support from volunteers in their home environments. Additional language development support systems in the form of programmes run by volunteers are important. This study describes and analyses the process of collaboration between six volunteers who are involved in languageliteracy programmes by examining how volunteers negotiate collaboration in promoting literacy development. This qualitative research study used a participatory action cycle design to investigate collaboration. A range of research methods such as focus groups, interviews, reflections and observations were used. Findings from this study provided insight into the identity of volunteers. They were people who had strong values in respect of literacy, a positive experience of volunteering, a sense of civic responsibility and an empathetic personality. The collaborative process was established through the presence of a strong common cause, vulnerability and trust among volunteers, a structured and well-led action cycle process, the development of self-reflection, and a passion to be change agents. Volunteers were able to problem solve and act to make changes to the intervention programme which included actions at a programme and volunteer level. The speechlanguage therapist (SLT’s) role was critical in a literacy-related intervention as a support for volunteers. The expertise of SLTs, namely knowledge in language and literacy development, was valued in streamlining the process of taking appropriate actions to enrich the literacy programme.